A chemical genetic approach demonstrates that MPK3/MPK6 activation and NADPH oxidase‐mediated oxidative burst are two independent signaling events in plant immunity. (17th December 2013) - Xu, Juan; Xie, Jie; Yan, Chengfei; Zou, Xiaoqin; Ren, Dongtao; Zhang, Shuqun
Summary Plant recognition of pathogen‐associated molecular patterns (PAMPs) such as bacterial flagellin‐derived flg22 triggers rapid activation of mitogen‐activated protein kinases (MAPKs) and generation of reactive oxygen species (ROS). Arabidopsis has at least four PAMP/pathogen‐responsive MAPKs: MPK3, MPK6, MPK4 and MPK11. It was speculated that these MAPKs may function downstream of ROS in plant immunity because of their activation by exogenously added H2O2. MPK3/MPK6 or their orthologs in other plant species have also been reported to be involved in the ROS burst from the plant respiratory burst oxidase homolog (Rboh) of the human neutrophil gp91phox. However, detailed genetic analysis is lacking. Using a chemical genetic approach, we generated a conditional loss‐of‐function mpk3 mpk6 double mutant. Consistent with results obtained using a conditionally rescued mpk3 mpk6 double mutant generated previously, the results obtained using the new conditional loss‐of‐function mpk3 mpk6 double mutant demonstrate that the flg22‐triggered ROS burst is independent of MPK3/MPK6. In Arabidopsis mutants lacking a functional AtRbohD, the flg22‐induced ROS burst was completely blocked. However, activation of MPK3/MPK6 was not affected. Based on these results, we conclude that the rapid ROS burst and MPK3/MPK6 activation are two independent early signaling events in plant immunity, downstream of FLS2. We also found that MPK4 negatively affects the flg22‐induced ROS burst. In addition, salicylic acid pre‐treatment enhances the AtRbohD‐mediated ROS burst, which is again independent of MPK3/MPK6 based on analysis of the mpk3 mpk6 double mutant. The establishment of an mpk3 mpk6 double mutant system using a chemical genetic approach provides a powerful tool to investigate the function of MPK3/MPK6 in the plant defense signaling pathway.